1990
DOI: 10.1073/pnas.87.12.4650
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the fusion domain of the human immunodeficiency virus type 1 envelope glycoprotein gp41.

Abstract: The human immunodeficiency virus transmembrane glycoprotein gp4l has at its amino terminus a strongly hydrophobic stretch of 28 amino acids flanked by a highly conserved series of polar amino acids. To investigate the role in syncytium formation of the hydrophobic amino terminus of gp4l and the polar border of this hydrophobic region, we introduced eight single-amino acid substitutions and one double-amino acid substitution in the amino-terminal 31 amino acids of gp4l. The mutant envelope glycoproteins were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
299
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(314 citation statements)
references
References 40 publications
14
299
0
1
Order By: Relevance
“…The HIV sequence in pKF1 was derived from the pNL4-3 molecular clone (Adachi et al, 1986). A StuIBamHI fragment from the env region of pKFI was replaced with the corresponding restriction fragment from pHenv41.2; this is derived from the BH10 clone of HIV-1, which has a Val to Glu mutation at the second amino acid of gp41 (Freed et al, 1990). The resulting pKF41.2 retroviral vector was used to transduce HeLa-CD4 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The HIV sequence in pKF1 was derived from the pNL4-3 molecular clone (Adachi et al, 1986). A StuIBamHI fragment from the env region of pKFI was replaced with the corresponding restriction fragment from pHenv41.2; this is derived from the BH10 clone of HIV-1, which has a Val to Glu mutation at the second amino acid of gp41 (Freed et al, 1990). The resulting pKF41.2 retroviral vector was used to transduce HeLa-CD4 cells.…”
Section: Methodsmentioning
confidence: 99%
“…The free peptide causes fusion of liposomes and erythrocytes, and numerous mutational studies have shown strong correlations between fusion peptide-induced liposome fusion and viral/host cell fusion (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…The ~170-residue ectodomain of gp41 lies outside HIV and is subdivided into a more C-terminal "soluble ectodomain" and a ~20-residue N-terminal fusion peptide (HFP) which is apolar and fairly conserved. The HFP is believed to interact with the target cell membrane after gp120 binds to cellular receptors and fusion is greatly disrupted by mutation or deletion of the HFP (10)(11)(12)(13).…”
mentioning
confidence: 99%